The role of entrepreneurial universities in smart cities - Santos, Domingos (2019)
The world population is increasingly urbanized. There is a need to analyze current smart urban challenges and opportunities, and to study how to incorporate smart systems into an agenda of urban competitiveness. The smart city approach is a recent theme, aiming at improving the quality of life of citizens in urban territories. Born like a bottom-up movement, it is now becoming critical in urban planning and development in cities all over the world. The smart city success depends on how cities achieve higher innovation profiles and competitiveness levels - on being entrepreneurial smart cities. Universities are one of the most significant cities' agents on building up active strategies to reinforce an entrepreneurial urban dynamics. Grounded on a vast and deep literature review on both scientific papers and practitioner or institutional reports, the paper tries to address the role the entrepreneurial university might bring to the formulation and implementation of smart cities strategies, pointing out to some instruments that can be used to enhance urban competitiveness and sustainability.